VARIACION CROMATICA EN ESPECIES DE EURYMETOPUM DEL GRUPO MODESTUM (COLEOPTERA: CLERIDAE: PHYLLOBAENINAE) - Solervicens, Jaime (Acta Entomológica Chilena, 2022)
Chromatic variation of Eurymetopum longulitm (Spinola, 1844) is described and a similar variation is recognized for Eurymetopum modestuni (Phil. y Phil., 1864). Both species show a chromatic morph which correspond to the color pattem of Eurymetopum testaceimembris Pie, 1950. The synonymy of E. modestum and E. testaceimembris is established on the basis of their chromatic and morphological similarity and geographical distribution.